Extensão Orientada a Aspectos para Interações Multi-participantes Confiáveis - Cassol, Luciano Azevedo; Zorzo, Avelino Francisco; Zampieri, André (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2006: Anais do VII Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2006.23346, 2006)
The use of mechanisms of fault tolerance in the development of systems is more and more frequent. A problem that can happen in these mechanism is the tangling among the fault tolerance mechanism and the system in development, as well as the fault tolerance code scattering in several points of the system. The use of aspect oriented programming can aid in the task of separating multi-dimensional interests in the software development. This work presents an extension of the framework for dependable multiparty interactions through the use of aspect oriented programming with the objective of obtaining transparency in its use in system development.